An observational study of Australian private practice physiotherapy consultations to explore the prescription of self‐management strategies. (3rd February 2017) - Peek, Kerry; Carey, Mariko; Mackenzie, Lisa; Sanson‐Fisher, Robert
Abstract: Objective: The aim of the study was to explore the types of self‐management strategies prescribed; the number of strategies and the overall length of time allocated to self‐management prescription, by consultation type and by injury location, in physiotherapy consultations. Methods: A cross‐sectional, observational study of 113 physiotherapist–patient consultations was undertaken. Regression analyses were used to determine whether consultation type and injury location were associated with the number of strategies prescribed and the length/fraction of time spent on self‐management. Results: A total of 108 patients (96%) were prescribed at least one self‐management strategy – commonly exercise and advice. The mean length of time spent on self‐management was 5.80 min. Common injury locations were the neck ( n  = 40) and lower back ( n  = 39). No statistically significant associations were observed between consultation type or injury location for either outcome (number of strategies and the length/fraction of time allocated to self‐management prescription). Conclusion: Physiotherapists regularly spend time prescribing self‐management strategies such as exercise, advice, and the use of heat or ice to patients receiving treatment linked to a range of injury locations. This suggests that self‐management is considered to be an important adjunct to in‐clinic physiotherapy. The practice implications of this are that clinicians should reflect on how self‐management strategies can be used to maximize patient outcomes, and whether the allocation of consultation time to self‐management is likely to optimize patient adherence to each strategy.